2015
DOI: 10.1108/lhs-03-2014-0015
|View full text |Cite
|
Sign up to set email alerts
|

Lean leadership: an ethnographic study

Abstract: In this case study, Lean leadership is specifically related to healthcare, but certain common leadership characteristics are relevant across all fields. This article shows the value of an auto-ethnographic view on management learning for the analysis of Lean leadership. The knowledge acquired through this research is based on the first author's experiences in fulfilling his role as a health-care leader. This may help the reader examining his/her own role and reflecting on what matters most in the field of Lean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(108 citation statements)
references
References 26 publications
3
102
0
3
Order By: Relevance
“…18,19 Two major lean principles that are applied "in the gemba" are seeking perfection and embracing scientific thinking. 20,21 A gemba walk or huddle is an opportunity for the team to gather where the work occurs and observe work as it happens. 18,22 Gemba huddles create a safe, nonpunitive forum for reflection, input, and observation.…”
mentioning
confidence: 99%
“…18,19 Two major lean principles that are applied "in the gemba" are seeking perfection and embracing scientific thinking. 20,21 A gemba walk or huddle is an opportunity for the team to gather where the work occurs and observe work as it happens. 18,22 Gemba huddles create a safe, nonpunitive forum for reflection, input, and observation.…”
mentioning
confidence: 99%
“…Additionally, research included two behaviors of leadership as contributing in lean success that is communicative (social) and directing as (micro manager). Similarly (Aij et al, 2015) emphasized that leader should perceived the intend of process by practical observation of the processes. The study also highlighted that communication with sub-ordinates, employee promotion and empowerment, trust on employees and openness to experience are the key factors of leadership which positively affect lean success.…”
Section: Lean and Leadershipmentioning
confidence: 99%
“…Aij et al [16] have reported three common leadership characteristics that are critical to successful lean implementation in the context of healthcare practice: 1) going to the gemba, 2) empowerment and trust, and 3) modesty and openness.…”
Section: Lean Leadership's Attributes and Practicesmentioning
confidence: 99%
“…Nevertheless, delving in the lean literature, one term is pervasive in many books, research papers, experts' speeches, and articles: 'Leadership'. Whether 'lack of leadership' is listed as a key failure factor or 'effective leadership' is listed as a key success factor, there is consensus on the role of leadership as an imperative in any lean turnaround [6,8,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%